2017
DOI: 10.18632/oncotarget.22436
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular miR-224 as a prognostic marker for clear cell renal cell carcinoma

Abstract: Exosome-miRNAs (exo-miR) have recently been identified as modulators of cancer progression and distant metastasis. We previously found that intracellular miR-224 is up-regulated and significantly related to cancer invasion and metastasis in clear cell renal cell carcinoma (ccRCC). We therefore investigated the role of exosome miR-224 in ccRCC and explored the interaction between intra- and extracellular miR-224 in renal cell carcinoma. To validate the method for isolating exosomes from blood samples or cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 48 publications
(61 reference statements)
1
41
0
Order By: Relevance
“…Functional experiments revealed an oncogenic role of miR-224 in RCC pathogenesis. Exosomes containing miR-224 from a metastatic RCC cell line that were added to a cell line of primary RCC enhanced proliferation and invasion and, moreover, increased the intracellular miR-224 levels in primary cell lines (Fujii et al, 2017). This indicates the importance of exosomal miRNAs in cancer progression (Fujii et al, 2017;Kulkarni et al, 2019).…”
Section: Cssmentioning
confidence: 85%
“…Functional experiments revealed an oncogenic role of miR-224 in RCC pathogenesis. Exosomes containing miR-224 from a metastatic RCC cell line that were added to a cell line of primary RCC enhanced proliferation and invasion and, moreover, increased the intracellular miR-224 levels in primary cell lines (Fujii et al, 2017). This indicates the importance of exosomal miRNAs in cancer progression (Fujii et al, 2017;Kulkarni et al, 2019).…”
Section: Cssmentioning
confidence: 85%
“…An increasing number of previous studies have demonstrated that miRNAs are dysregulated in approximately all types of human malignancy, including ccRCC (13)(14)(15). miRNA (miR)-19a (16), miR-224 (17), miR-1274a (18) and miR-543 (19) were upregulated in ccRCC, whereas, miR-30a (20), miR-200a (21), miR-384 (22) and miR-411 (23) were downregulated. These aberrantly expressed miRNAs are implicated in the oncogenesis and progression of ccRCC, and regulate various crucial biological processes, including cell proliferation, apoptosis, metastasis and angiogenesis (13,24).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other more recent studies have reported that urinary exosomal miR-30c-5p and miR-204-5p might serve as the diagnostic markers for early-stage ccRCC (in a human study) and Xp11.2 translocation RCC (in a murine model), respectively (Kurahashi et al, 2019;Song et al, 2019). In addition, two consistent studies in humans have revealed that serum exosomal miR-224 and miR-210 could serve as the prognostic and diagnostic biomarkers for ccRCC (Fujii et al, 2017;Wang X. et al, 2019). Furthermore, serum exosomal miR-126-3p, miR-17-5p and miR-21-3p were decreased 1-day after cryoablation of RCC in a murine model and might be used as the biomarker for monitoring therapeutic outcome in RCC .…”
Section: Renal Cell Carcinomamentioning
confidence: 64%